INVESTMENT DECISION ANALYSIS OF BONTANG LNG HUB PROJECT - Permana, Dedi
PT Badak NGL (“BADAK LNG”) has been producing LNG since 1977 which production is depended on the amount of feed gas available in the region. It is estimated a trend of decreasing feed gas supply for the existing liquefaction plant which deficit will occurs in 2026. As the result, the existing 6 units LNG storage tanks, with a total capacity of 600,000 m3, and jetty facility are foreseen to be under-utilized starting 2026. Therefore, Badak LNG have the intention to convert the existing export terminal into LNG receiving and hub terminal (“LNG Hub Project”) as new business unit.